Introducing an R package for luminescence dating analysis - Kreutzer, Sebastian; Schmidt, Christoph; Fuchs, Margret C.; Dietze, Michael; Fischer, Manfred; Fuchs, Markus (Ancient TL, 2012)
For routine luminescence dating applications the commonly used Risø readers are bundled with analysis software, such as Viewer or Analyst. These software solutions are appropriate for most of the regular dating and publication jobs, and enable assessment of luminescence characteristics and provide basic statistical data treatment. However, for further statistical analysis and data treatments, this software may reach its limits. In such cases, open programming languages are a more appropriate approach. Here, we present the R package ‘Luminescence’ for a more flexible handling of luminescence data and related plotting purposes, using the statistical programming language R. The R language as well as the package and the source code are provided under the General Public License (GPL) conditions and are available for free. The basic functionality of the package is described along with three application examples. This package is not an alternative to the existing software (Analyst, Viewer) but may provide a collection of additional tools to analyse luminescence data and serve as a platform for further contributions
Gesehen am 27.03.2025